Supplier Relationship Management Practices of Ministries, Department and Agencies (MDA’s) in Ghana (Supplier Perspective): (A Case of Ghana Highway Authority) - Addae, Clement (2016)
A dissertation Submitted to the Department of Building Technology, College of Art and Built Environment in partial fulfillment of the requirement for the degree of Master of Science in Procurement Management, 2015